Real-world Outcomes and Factors Predicting Survival and Completion of Radium 223 in Metastatic Castrate-resistant Prostate Cancer. Issue 9 (September 2018) - Parikh, S.; Murray, L.; Kenning, L.; Bottomley, D.; Din, O.; Dixit, S.; Ferguson, C.; Handforth, C.; Joseph, L.; Mokhtar, D.; White, L.; Wright, G.; et al.
Abstract: Aims: To analyse outcomes in metastatic castrate-resistant prostate cancer (mCRPC) patients treated with radium 223 (Ra-223) across the Yorkshire and Humber Cancer Network. Materials and methods: A regional, multicentre, retrospective cohort study of 189 men undergoing Ra-223 for mCRPC between March 2014 and April 2017 was undertaken. Factors predicting overall survival and completion of planned treatment were assessed. Results: The median overall survival for the entire cohort was 10.5 months. Those completing five to six cycles of Ra-223 had a higher overall survival of 18.6 months. On multivariable analysis, four factors remained independent significant predictors of overall survival: age ( P = 0.005, hazard ratio 1.07 [1.02–1.12]); number of cycles of Ra-223: 5–6 versus 1–4 ( P ≤ 0.001, hazard ratio 0.10 [0.005–0.20]); baseline alkaline phosphatase ( P = 0.044, hazard ratio 1.06 [1.002–1.12]); neutrophil-to-lymphocyte ratio ( P = 0.033, hazard ratio 1.19 [1.01–1.40]). Baseline performance status 0 versus 2 ( P = 0.026, odds ratio 0.080 [0.001–0.74]) and higher baseline haemoglobin ( P = 0.028, odds ratio 1.04 [1.004–1.074]) were independent predictors of the completion of five to six cycles of Ra-223. Conclusions: Younger age, completion of five to six cycles of Ra-223, lower alkaline phosphatase and neutrophil-to-lymphocyte ratio are predictors of overall survival. This is the first study to report neutrophil-to-lymphocyte ratio as an independent predictor of overall survival in a Ra-223 cohort. Good performance status and higher baseline haemoglobin predict the completion of five to six cycles of Ra-223. Highlights: Regional audit of recently introduced radium 223 service shows survival outcomes similar to previously published. Good performance state and nearer normal haemoglobin predict likelihood of completing planned treatment. Neutrophil-to-lymphocyte ratio is an independent predictor of survival.